Las Matras Block, Central Argentina (37°S-67°w): The southernmost Cuyania terrane and its relationship with the Famatinian orogeny - Sato, Ana Maria (2004)
The Las Matras Block in Central Argentina constitutes the southernmost part of the Cuyania terrane, which was accreted to the southwestern margin of Gondwana during the Early to Mid Ordovician Famatinian orogeny. The Grenville-aged rocks of the Las Matras Block are represented by the tonalitic to trondhjemitic Las Matras pluton. A new U-Pb conventional zircon age of 1244±42 Ma confirms previous Sm-Nd and Rb-Sr isochron ages of this pluton. Mineral composition data are consistent with the tonalitic-trondhjemitic character of the pluton, and constrain its emplacement level to 1.9 to 2.6 kb. This shallow level of emplacement and the undeformed character of the pluton are distinctive features of this southernmost basement. A regional comparison indicates that the igneous-metamorphic evolution of the Grenville-aged basement rocks of the Cuyania terrane occurred over a period of more than 200 million years, with ages older than 1200 Ma up to those close to 1000 Ma. The shallowest crustal level is found in Las Matras, suggesting a southward shallowing of the exposed level of basement. The deformation and metamorphism associated with the collisional Famatinian orogeny affect both the Cuyania terrane and the adjacent western margin of Gondwana, and the Gondwana margin was also the locus of the related arc magmatism, but the compressive effects of the collision decrease in intensity toward the south. The Famatinian metamorphism and magmatism continue even further south into the Patagonia region, but the southern continuity of the Cuyania terrane into this region remains uncertain.